Impact of Financial Inclusion on Inclusive Growth: An Empirical Study of Nigeria - Afolabi, Joseph Olarewaju (Asian Journal of Economics and Empirical Research, 2020)
The study investigates the effect of financial inclusion on inclusive growth in Nigeria covering the periods of 1981 to 2017. It adopts the Auto-Regressive Distributed Lag (ARDL) model, using annual series from CBN statistical bulletin and World Development Indicators (WDI). The variables adopted include; rural loan, number of bank branches, money supply-GDP ratio, private sector credit to GDP ratio and GDP per capita. The study found financial inclusion, in the form of rural loan, number of bank branches and level of liquidity have a positive and significant effect on inclusive growth in the short and long run, while interest rate impede inclusive growth. The study recommends more and improved financial services be made available to rural dwellers and the economy in general to help them participate and contribute more to national productivity. However, these financial services should be carefully monitored to make sure they are used productively. This should help reduce inequality in the country and put the country in a path of inclusive growth.